An Empirical Study about the Vision of a Tutoring Team on the Distance Learning Process - Siebra, Clauirton; Alencar, Denise; Guimarães, Ana Paula; Silva, Jefferson (Anais do Workshop sobre Educação em Computação (WEI); 2015: Anais do XXIII Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2015.10223, 2015)
Tutors are a fundamental element of the Distance Learning (DL) process. In fact, they complement the role of lecturers, giving a closer assistance to DL students. Considering the importance of tutors, this work investigates the DL process from their perspective. To that end, an empirical analysis was carried out via questionnaires and interviews, which were applied to 28 distance and 17 local tutors of a DL computing degree course. The collected information was analyzed and classified as a way to stress the main features, problems and solutions that have been applied along the past semesters. A list of suggestions to improve the educational environment/tool and pedagogic method was also elaborated as a result from this research.